Inelastic neutron scattering: a novel approach towards determination of equilibrium isotopic fractionation factors. Size effects on heat capacity and beta-factor of diamond. Issue 23 (5th June 2020) - Shiryaev, Andrey A.; Polyakov, Veniamin B.; Rols, Stephane; Rivera, Antonio; Shenderova, Olga
Abstract : Inelastic neutron scattering is a novel method for determination of thermodynamic and isotopic properties of nanoparticles. Influence of surface can be evaluated. The C v of nanodiamonds is higher and the β -factor is lower than those of bulk diamond. Abstract : A new experimental method for the determination of equilibrium isotopic properties of substances based on inelastic neutron scattering (INS) is proposed. We present a mathematical formalism, which allows the calculation of the beta-factor of single-element solids based on INS-derived Phonon Density of States (PDOS). PDOS data for nanodiamonds of widely different sizes and of macroscopic diamond were determined from inelastic neutron scattering experiments. This allowed the determination of heat capacities and, for the first time, β -factors of the diamond nanoparticles. We demonstrate a considerable size-dependent increase of the heat capacities and decrease of the beta-factors for nanodiamonds relative to bulk diamond. Contributions of surface impurities/phases and phonon confinement to the size effects are evaluated. Applications in the formation of diamond nanoparticles in nature are briefly discussed.